1996
DOI: 10.1113/jphysiol.1996.sp021384
|View full text |Cite
|
Sign up to set email alerts
|

Myofibrillar ATPase activity in skinned human skeletal muscle fibres: fibre type and temperature dependence.

Abstract: 1. Myofibrillar ATP consumption and isometric tension (PO) were determined in chemically skinned skeletal muscle fibres from human rectus abdominis and vastus lateralis muscle. Fibres were classified in four groups (I, II A, II B, II A/B or mixed) based on myosin heavy chain composition.2. ATP consumption (± S.E.M.) at 200C varied from 0-41 + 0-06 mmol F-1 s-5 in type IIB fibres (n = 5) to 0I10 + 0 01 mmol 1-' s-' in type I fibres (n = 13). 3. The ratio between ATPase activity and PO (tension cost) differed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
195
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(229 citation statements)
references
References 27 publications
30
195
4
Order By: Relevance
“…However, there is extensive evidence that intact mammalian fibres maintain their contractile performance in vitro at temperatures between 30 and 37°C (Barclay, 1994;Close, 1964Close, , 1965Close and Luff, 1974;Luff, 1981;McCrorey et al, 1966;Ranatunga, 1982) and lizard muscle performs well at 40°C . In contrast, skinned fibre performance declines rapidly with repeated activation, which prevents reliable measurements of maximum power Stienen et al, 1996). We encountered the same problem in the current set of experiments with skinned rabbit fibres at 33°C.…”
Section: Discussionmentioning
confidence: 71%
“…However, there is extensive evidence that intact mammalian fibres maintain their contractile performance in vitro at temperatures between 30 and 37°C (Barclay, 1994;Close, 1964Close, , 1965Close and Luff, 1974;Luff, 1981;McCrorey et al, 1966;Ranatunga, 1982) and lizard muscle performs well at 40°C . In contrast, skinned fibre performance declines rapidly with repeated activation, which prevents reliable measurements of maximum power Stienen et al, 1996). We encountered the same problem in the current set of experiments with skinned rabbit fibres at 33°C.…”
Section: Discussionmentioning
confidence: 71%
“…1A, the slow fibres are oxidative and have more mitochondria and myoglobin, whereas fast fibres are more glycolytic and exhibit more glycogen and phosphocreatine. Muscle measurements in the steady state or during developed tension revealed that ATPase activity was higher in fast type IIb fibres than that in IIa and IIx fibres, which all have higher activity than slow type I fibres (Stienen et al 1996). During muscle contraction, the ATP hydrolysis rate increases in all fibre types proportionally to the ATP production speed of each fibre type, which is higher in fast fibres than in the slow ones.…”
Section: Introductionmentioning
confidence: 96%
“…This difference in energy utilization between fibre types undoubtedly reflects differences in cross-bridge cycling kinetics and actomyosin ATPase activities of the different MyHC isoforms [16,[55][56][57][58].…”
Section: Relationship Between Myhc Isoform Expression and Atp Consumpmentioning
confidence: 99%